2018
DOI: 10.1038/s41389-018-0094-y
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of tumor progression and cancer stemness by MUC15 in thyroid cancer via the GPCR/ERK and integrin-FAK signaling pathways

Abstract: Thyroid cancer is the fifth most common cancer diagnosed in women worldwide. Notwithstanding advancements in the prognosis and treatment of thyroid cancer, 10–20% of thyroid cancer patients develops chemotherapeutic resistance and experience relapse. According to previous reports and TCGA database, MUC15 (MUCIN 15) upregulation is highly correlated with thyroid cancer progression. However, the role of MUC15 in tumor progression and metastasis is unclear. This study aimed to investigate factors mediating cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…MUC15 also encodes a membrane-bound protein, which could promote cell proliferation, cell-extracellular matrix adhesion, colony forming ability, and invasion in colon cancer cells (Huang et al, 2009). Its overexpression is significantly correlated with diverse cancers (Pallesen et al, 2002;Shyu et al, 2007;Huang et al, 2009;Nam et al, 2011;Wang et al, 2013;Choi et al, 2018). However, it was also found that the expression of MUC15 decreased in hepatocellular carcinoma cells and negatively regulated metastasis of hepatocellular carcinoma (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC15 also encodes a membrane-bound protein, which could promote cell proliferation, cell-extracellular matrix adhesion, colony forming ability, and invasion in colon cancer cells (Huang et al, 2009). Its overexpression is significantly correlated with diverse cancers (Pallesen et al, 2002;Shyu et al, 2007;Huang et al, 2009;Nam et al, 2011;Wang et al, 2013;Choi et al, 2018). However, it was also found that the expression of MUC15 decreased in hepatocellular carcinoma cells and negatively regulated metastasis of hepatocellular carcinoma (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MUC4 promotes carcinogenetic progression and has been proposed as a promising biomarker for pancreatic, ovarian, esophagus, and lung cancers (Kaur et al, 2013;Jonckheere and Van Seuningen, 2018). MUC15 overexpression is significantly correlated with several types of cancers, including colon cancer, hepatocellular carcinoma, and thyroid cancer (Huang et al, 2009;Nam et al, 2011;Wang et al, 2013;Choi et al, 2018). Moreover, MUC4/MUC16/MUC20 highexpression signature was very recently reported to be correlated with poor overall survival (OS) in several types of digestive cancers including pancreatic, colon, and GCs (Jonckheere and Van Seuningen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Yang [ 32 ] showed the MUC15 overexpression was correlated with cancer progression and can be used as a marker for poor prognosis in glioma patients. In thyroid cancer, Choi [ 18 ] showed that MUC15 has a vital function in sphere formation of cancer cells and activates ERK by FAK and GPCR/cAMP pathways. The above studies suggested that MUC15 enhances the occurrence, development, and invasion in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that MUC15 upregulation significantly contributes to migration and invasion in colon cancer, thyroid cancer, and glioma [ 16 18 ]. In our study, we also demonstrated that MUC15 could enhance cell motility in PDAC by the strategy of silencing or overexpressing MUC15.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the results from the Venn diagram, all genes were included in RRA result. These iDEGs were predominantly enriched in the pathways 'PI3K-Akt signaling pathway', 'focal adhesion', 'ECM-receptor interaction' and the 'calcium signaling pathway' (24)(25)(26). A total of 7 hub genes were identified from the PPI network, which was composed of 493 iDEGs.…”
Section: Discussionmentioning
confidence: 99%